Optimizing Early Childhood Ecoliteracy: An Experimental Study - Sitorus, Junida Fitriani; Sit, Masganti; Sitorus, Ahmad Syukri; Syafriani, Angela (Universitas Negeri Makassar, 2025)
This study investigates the effects of experiential learning strategies, namely science experiments, outdoor learning activities, and problem-solving skills, on the ecoliteracy of early childhood learners. Employing a quasi-experimental quantitative design with a 2x2 factorial arrangement. The number of students who became research participants was 50, consisting of 20 boys and 30 girls. The research was conducted among students enrolled in early childhood education institutions (RA) in Deli Serdang. The results demonstrate that instructional strategies significantly improve children's environmental knowledge, attitudes, and environmental behavior care. Moreover, children with higher levels of problem-solving ability exhibited greater ecoliteracy. These findings emphasize the critical role of integrating active learning methods and the development of higher-order thinking skills from an early age to foster environmentally responsible future generations.